Job satisfaction of primary care physicians in Switzerland: an observational study - Götz, Katja; Jossen, Marianne; Szecsenyi, Joachim; Rosemann, Thomas; Hahn, Karolin; Hess, Sigrid (Family practice, 2016)
AbstractBackground.. Job satisfaction of physicians is an important issue for performance of a health care system. The aim of the study was to evaluate the job
Gesehen am 25.06.2020